System integration of magnetic medical microrobots: from design to control - Zhou, Junjian; Li, Mengyue; Li, Na; Zhou, Yuting; Wang, Jingyi; Jiao, Niandong (Frontiers in Robotics and AI, 2023)
Magnetic microrobots are ideal for medical applications owing to their deep tissue penetration, precise control, and flexible movement. After decades of development, various magnetic microrobots have been used to achieve medical functions such as targeted delivery, cell manipulation, and minimally invasive surgery. This review introduces the research status and latest progress in the design and control systems of magnetic medical microrobots from a system integration perspective and summarizes the advantages and limitations of the research to provide a reference for developers. Finally, the future development direction of magnetic medical microrobot design and control systems are discussed.